Differences in Safety of Nonsteroidal Antiinflammatory Drugs in Patients With Osteoarthritis and Patients With Rheumatoid Arthritis: A Randomized Clinical Trial. Issue 4 (29th March 2018) - Solomon, Daniel H.; Husni, M. Elaine; Wolski, Katherine E.; Wisniewski, Lisa M.; Borer, Jeffrey S.; Graham, David Y.; Libby, Peter; Lincoff, A. Michael; Lüscher, Thomas F.; Menon, Venu; Yeomans, Neville D.; Wang, Qiuqing; et al.
Abstract : Objective: To determine the relative risks of cardiovascular (CV), gastrointestinal (GI), and renal adverse events during long‐term treatment with celecoxib, compared with ibuprofen and naproxen, in patients with osteoarthritis (OA) and patients with rheumatoid arthritis (RA). Methods: A total of 24, 081 patients with OA or RA who had a moderate or high risk for CV disease were enrolled internationally into a double‐blind randomized controlled trial. Interventions included celecoxib at a dosage of 100–200 mg twice daily, ibuprofen at a dosage of 600–800 mg 3 times daily, or naproxen at a dosage of 375–500 mg twice daily. The main outcomes were the first occurrence of a major adverse CV event, GI event, or renal event, and mortality. Results: In the subgroup of patients with OA, the risk of a major adverse CV event was significantly reduced when celecoxib was compared with ibuprofen (hazard ratio [HR] 0.84, 95% confidence interval [95% CI] 0.72–0.99), but no significant difference was observed when celecoxib was compared with naproxen. In the RA subgroup, comparisons of celecoxib versus ibuprofen and celecoxib versus naproxen for the risk of major adverse CV events revealed HRs of 1.06 (95% CI 0.69–1.63) and 1.22 (95% CI 0.78–1.92), respectively. In the OA subgroup, comparisons of celecoxib versus ibuprofen for the risk of GI events showed an HR of 0.68 (95% CI 0.51–0.91), and a comparison of celecoxib versus naproxen showed an HR of 0.73 (95% CI 0.55–0.98). Duplicate comparisons in patients with RA revealed HRs of 0.48 (95% CI 0.22–1.07) and 0.54 (95% CI 0.24–1.24), respectively. In patients with OA, a comparison of celecoxib versus ibuprofen for the risk of renal events showed an HR of 0.58 (95% CI 0.40–0.82). In patients with RA, celecoxib treatment was associated with significantly lower mortality compared with naproxen treatment (HR 0.47, 95% CI 0.25–0.88). Conclusion: Treatment with celecoxib at approved dosages conferred a similar or lower risk of CV, GI, and renal adverse events compared with treatment with ibuprofen or naproxen in patients with OA and patients with RA.